2021
DOI: 10.1007/s00382-021-05787-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal prediction of the boreal winter stratosphere

Abstract: The predictability of the Northern Hemisphere stratosphere and its underlying dynamics are investigated in five state-of-the-art seasonal prediction systems from the Copernicus Climate Change Service (C3S) multi-model database. Special attention is devoted to the connection between the stratospheric polar vortex (SPV) and lower-stratosphere wave activity (LSWA). We find that in winter (December to February) dynamical forecasts initialised on the first of November are considerably more skilful than empirical fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 113 publications
9
31
0
Order By: Relevance
“…A potential reason for the lack of a predictable signal in NAO− could lie in the role of stratospheric sudden warmings (SSWs), which are known to induce negative NAO states (Baldwin and Dunkerton, 2001;Hitchcock and Simpson, 2014;Domeisen et al, 2020). Portal et al (2021) have shown that seasonal forecast models, including the SEAS5 model studied here, tend to overpredict the SSW response to ENSO. Consistent with that, there is a strong NAO− response to ENSO (Figure 8), which is not seen in observations.…”
Section: Regimementioning
confidence: 88%
“…A potential reason for the lack of a predictable signal in NAO− could lie in the role of stratospheric sudden warmings (SSWs), which are known to induce negative NAO states (Baldwin and Dunkerton, 2001;Hitchcock and Simpson, 2014;Domeisen et al, 2020). Portal et al (2021) have shown that seasonal forecast models, including the SEAS5 model studied here, tend to overpredict the SSW response to ENSO. Consistent with that, there is a strong NAO− response to ENSO (Figure 8), which is not seen in observations.…”
Section: Regimementioning
confidence: 88%
“…Note that since the figure is composited based on initializations, the probabilities for March include verification times in April, and so the corresponding probabilities for easterly winds are likely influenced by final warmings. Regardless, this seasonal cycle is only partially reproduced in the subseasonal models, which particularly underestimate the probability of events for December and January initializations at weeks 3 and 4, and of in January, and seasonal prediction models, which also fail to reproduce the SSW peak in January (Portal et al, 2021) despite the seasonal average of SSWs often being well reproduced (Domeisen et al, 2015). Interestingly, the NCEP system consistently predicts a higher occurrence of easterly winds than other systems.…”
Section: Northern Hemisphere Polar Vortex Variabilitymentioning
confidence: 94%
“…Indeed, tropospheric biases identified independently of the stratosphere can sometimes be traced back to stratospheric anomalies in subseasonal forecasts; in the ECMWF extended-range prediction system, the persistence of the NAO was found to be constrained too strongly by the state of the polar vortex at initialization (Kolstad et al, 2020). Since stratospheric variability and extreme events are primarily governed by wave-mean flow interactions, biases in wave driving due to either resolved or parameterized processes can lead to biases in the mean state of the stratosphere, which can further alter its response to subsequent forcing (McLandress et al, 2012;Richter et al, 2014) and limit stratospheric predictability (Portal et al, 2021). More fundamentally, a model's vertical resolution in the stratosphere can influence its ability to realistically represent the stratosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9c), our analysis reveals that the snow cover anomaly reinforces the Ural ridge, allowing for increased wave flux into the stratosphere. This location of a tropospheric ridge interferes constructively with climatological stationary wave-1 and wave-2 patterns (Garfinkel et al, 2010) and seems to be key for a skilled forecast of the polar winter stratosphere (Portal et al, 2021).…”
Section: Discussionmentioning
confidence: 94%